Modelamiento de un Robot de Cinco Grados de Libertad en un Módulo de Manufactura Flexible. (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2011)
The flexible manufacturing module of the CNC Lab automation engineering program includes within its main components two CNC machines, which perform machining by turning and milling. For the positioning of these parts, a control methodology is applied to the CRS A255 robotic arm, using LabView® as a graphic interface. In order to calculate the forward, inverse and differential kinematics, the models associated to that methodology are developed. Validation of the models is performed after that moving the robot using the software, which recognize each joint and shows data as link´s speed, endpoint of the end effector, angular displacement of each link and the paths for the positioning of the parts in the CNC machines. The accuracy for the arm to reach the endpoint is assessed, validating the model experimentally, obtaining error values of 1.19% for direct kinematics and 3% for inverse kinematics, values that are acceptable for a good position and confirming that the paths of motion that were established are adequate.
Keywords: Robot; modeling; manufacturing; kinematics